2020
DOI: 10.1111/jace.17328
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of pure and mixed rare earth silicates against calcium‐magnesium‐aluminosilicate (CMAS): A comparative study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 58 publications
0
23
0
1
Order By: Relevance
“…Component analysis confirms the presence of CMAS. Sleeper, 36 14 a mixture of Yb monosilicate and disilicate was studied for resistance to CMAS. Their results showed that the thickness of the needle-shaped apatite was thin, but the fringe was thicker where the silicate mixture was uniformly mixed.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Component analysis confirms the presence of CMAS. Sleeper, 36 14 a mixture of Yb monosilicate and disilicate was studied for resistance to CMAS. Their results showed that the thickness of the needle-shaped apatite was thin, but the fringe was thicker where the silicate mixture was uniformly mixed.…”
Section: Characterizationmentioning
confidence: 99%
“…The main corrosion factor is Ca, and it is thought that the Ca content of CMAS is higher than that of volcanic ash, and more of the Ca 2 Gd 8 (SiO 4 ) 6 O 2 (apatite) phase is formed by reacting with Gd 2 SiO 5 . Wolf et al 14 Yb 3+ (0.985 Å), which has a larger ionic radius than Sc 3+ (0.870 Å), provides a more reactive driving force for Ca. As compared with Gd 3+ (1.05 Å), the theory that the thickness of the reaction layer (apatite) becomes thicker as the size of ions increases is supported.…”
Section: Characterizationmentioning
confidence: 99%
“…23,[31][32][33][34][35][36][37][38] T in these cases to determine the resin flow ing times corresponding to different infilt Preceramic polycarbosilane polymers as precursors to make ceramic fibers 10,3 trix. [7][8][9]40,41 The chemical and volume ch pany ceramization of the polymer during documented in several studies. For exam 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Conflicting observations on the stability of Yb 2 Si 2 O 7 materials in contact with CMAS have been reported, as some works observed the formation of the crystalline apatite phase Ca 2 Yb 8 (SiO 4 ) 6 O 2 while others did not. [36][37][38][39][40][41] However, the interaction of Yb 2 Si 2 O 7 with Na 2 SO 4 deposits, another known source of depositinduced degradation in turbine engines, has received very little attention in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to investigate the hot corrosion behavior between the EBCs and NaVO 3 . Up to now, many studies have been conducted on thermal shock performance [12], calcia-magnesiaaluminosilicate (CMAS) corrosion [13,14] and wateroxygen corrosion [15,16] for Yb 2 Si 2 O 7 . Recently, Fan et al [17] investigated the hot corrosion behavior of γ-Y 2 Si 2 O 7 in the molten salt of Na 2 SO 4 and V 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%